A Narrative Review on Mindfulness Practices in Optimizing Performance Among Sports Individuals - Vinodhkumar, Ramalingam; Keng, Cheong Soon; Lee, Poh Foong (Horizon Publisher India, 2021)
Mindfulness practice has become an increasingly popular intervention in optimizing athletic performance in sports. Numerous studies have reported on applying mindfulness for improving the performance of various sports such as tennis, table tennis, shooting, cricket, archery, golf, running, hockey, swimming, and cycling. This narrative review addresses different existing mindfulness programs that enhance sports performance, the outcome measures of mindfulness therapy, and identifies the anxiety and depression that affect the performance of sports individuals. To cope with the issues, the efficacy of mindfulness in performance enhancement and future research directions on mindfulness needs attention.